Androgen receptor polyglutamine tract length in Egyptian male breast cancer patients - Gilbert, Samuel F. (Breast Cancer Res Treat, 2011)
Male Breast Cancer (MBC) is a rare disease in the U.S., accounting for less than 1% of all breast cancers. Rates of MBC in Africa are more variable than in the U.S., therefore, understanding the risk factors involved in a population like Egypt can clarify the nature of MBC. The polyglutamine tract (QT) is a variable region of the androgen receptor (AR), a nuclear receptor which is important in modulating androgen actions and generally inhibits growth in breast tissue. It is hypothesized that a long QT results in weaker AR activity over the lifetime, resulting in less AR mediated control over cellular division and higher risk of MBC. As a corollary, we expect to see a distribution skewed toward longer QTs in MBC patients compared to controls and overall relatively longer QT’s in populations with higher rates of MBC. This study aimed to investigate for the first time the distribution of AR QT lengths among MBC patients in Egypt. Paraffin-embedded tumor tissues from 44 Egyptian MBC patients were analyzed for this polymorphism. Amplification followed by fragment length analysis revealed QT length. For the control series, blood from 43 Egyptian males without a family or personal history of breast or prostate cancers was collected and analyzed similarly. There was no significant difference between patients and controls with respect to mean QT length (P = 0.84; means were 19.5 ± 2.8 and 19.3 ± 4.2, for patients and controls, respectively). Though, short QT lengths were more prevalent among controls (14.0%), but almost absent in cases (2.3%). Although the mean lengths were not different in cases and controls, the near absence of short tracts in cases suggests a possible protective effect of very short QT lengths against MBC. In populations in which there is variable incidence of MBC by region, investigations of the distribution of AR QT lengths are warranted to further delineate its role as a risk factor in MBC.